The effect of chemotherapy on sacral chordoma in low resources country: A case report of a rare disease (Indian Journal of Case Reports, 2021)
Chordoma is a rare malignant tumor that is more prevalent among males than females. The diagnosis is usually confirmed by imaging and histopathological examination. Surgery is the mainstay of therapy but in some conditions such as metastasis chordoma or poor patient’s health, radiotherapy and chemotherapy can be carried out. We reported a case of metastatic sacral chordoma in a 58-year-old male patient, in which chemotherapy was chosen. Chemotherapy was given three times but did not show significant results.